A People and A Nation: A History of the United States - Norton, Mary Beth. (Boston Houghton MIfflin Company, 1984)
A few years ago six historians set out to provide students and instructors with a comprehensive survey that tells the whole story of American history, both the public and the private sides of American life. This brief edition covers events to the present time.
Keywords: History